2015
DOI: 10.2516/ogst/2014061
|View full text |Cite
|
Sign up to set email alerts
|

Solar Hydrogen Reaching Maturity

Abstract: -Increasingly vast research efforts are devoted to the development of materials and processes for solar hydrogen production by light-driven dissociation of water into oxygen and hydrogen. Storage of solar energy in chemical bonds resolves the issues associated with the intermittent nature of sunlight, by decoupling energy generation and consumption. This paper investigates recent advances and prospects in solar hydrogen processes that are reaching market readiness. Future energy scenarios involving solar hydro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
27
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 54 publications
0
27
0
Order By: Relevance
“…However, this seawater battery charge needs high voltage, whereas the current density is a low priority, and photoanodes provide higher photovoltage than most known PV devices. We were able to operate completely bias-free, spontaneous solar charge of seawater battery for 8 h. However, for practical applications, it should be much longer than 10 years (Rongé et al., 2015). Previous studies on the stability of PEs for water oxidation demonstrated stability for less than 2,000 h (Sun et al., 2015, Zhou et al., 2016), and thus the stability issue should be addressed in further developments of PEC devices in addition to efficiency.…”
Section: Discussionmentioning
confidence: 99%
“…However, this seawater battery charge needs high voltage, whereas the current density is a low priority, and photoanodes provide higher photovoltage than most known PV devices. We were able to operate completely bias-free, spontaneous solar charge of seawater battery for 8 h. However, for practical applications, it should be much longer than 10 years (Rongé et al., 2015). Previous studies on the stability of PEs for water oxidation demonstrated stability for less than 2,000 h (Sun et al., 2015, Zhou et al., 2016), and thus the stability issue should be addressed in further developments of PEC devices in addition to efficiency.…”
Section: Discussionmentioning
confidence: 99%
“…3,24 Consequently, several approaches of photo-and electrocatalyst/photovoltaic devices combinations have been designed and tested, leading to higher Solar-To-Fuel (STF) efficiencies, compared to their photoelectrochemical (PEC) counterparts based on photoactive electrodes, where the photovoltage is generated at the semiconductor-liquid junction (SCLJ). 25 As a relevant example, an unprecedented 17.5% STH efficiency has been recently reported for self-driven solar water-splitting, using a tandem PV-photocathode system. 26 From the technological point of view, compared to wired systems, the photovoltaic-electrocatalyst (PV-EC) integrated architectures where both components are intimately connected, offer a compact and less complex design for the realization of an ''artificial leaf'' for practical solar fuel production.…”
Section: Introductionmentioning
confidence: 99%
“…Solar power is by far the biggest source of renewable energy available [1]. Capturing this solar energy and storing it in chemical bonds is acknowledged as a way to provide energy security [2]. Solar hydrogen generation fits well in this strategy [3], and it allows to store solar energy on a seasonal timespan [4,5].…”
Section: Introductionmentioning
confidence: 99%